Gambaran Sikap Siswa SMA Negeri Kota Semarang Mengenai Iklan Rokok Di Kota Semarang - Mifta Nur Dwiyani; Kusyogo Cahyo; Besar Tirto Husodo; Bagoes Widjanarko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Population in Central Java who having smoking habit everyday, most of them are at young age, which is on 41,6% (15-19 years old). Smoking habit is not only caused by internal factor, but also it is caused by external factor. One of constributing factor that supports smoking behaviour is environmental factor, such as cigarette advertisement. Although there has been specific regulation governing the advertisement of cigarettes, but there are still many high school students that exposed by cigarette advertisements, either through electronic media or other printed media, as well as through the promotion of cigarettes. The method of this research was using quantitative with cross sectional approach. The population was all of State Senior High School in Semarang, totalling 16 of State Senior High School, and 17.811 as the population, 100 students was choosen as research sample, the sampling technique was simple random sampling. People and samples was taken as many as 140 people using saturation sampling method. The source data of this research were using primary and secondary data. The data analysis was using univariate analysis. Most respondents classified into exposure category towards cigarette advertisements (81%), respondents mentioned that the cigarette advertisements was attractive (69%), the behaviour of State Senior High of Semarang city regarding cigarette advertisements were, most of them disagree (42%), and the rest was agree (42% ). Therefore, from the result of the research, it was needed tighter supervision regarding the implementation of the regulation towards cigarette advertisements in order to reduce the number of students who are exposed by cigarette advertisements, either through television or printed media or through promotion conducted by tobacco companies that usually held events that attract young people, hence, most of them who attendeded cigarettes promotional event is teenagers who are still attending school.